1995
DOI: 10.1007/bf00197639
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of the circular dumbbell d〈pCGC-TT-GCG-TT〉: Structure determination and molecular dynamics

Abstract: The circular DNA decamer 5'-d-3' was studied in solution by means of NMR spectroscopy and molecular dynamics in H2O. At a temperature of 269 K, a 50/50 mixture of two dumbbell structures (denoted L2L2 and L2L4) is present. The L2L2 form contains three Watson-Crick C-G base pairs and two two-residue loops is opposite parts of the molecule. On raising the temperature from 269 K to 314 K, the L2L4 conformer becomes increasingly dominant (95% at 314 K). This conformer has a partially disrupted G(an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 65 publications
(65 reference statements)
7
51
1
Order By: Relevance
“…6 A "weakly constrained" MD simulation of the HPAC hairpin in water (wMD) was performed at 300 K, with an arbitrarily choosen force constant K dc of 0.4 kJ/ mol ⅐ Å 2 on the distance constraints and E tc 0.4 kJ/mol on torsion angles. The molecule was immersed in a rectangular box of Monte Carlo TIP3P water molecules.…”
Section: Restrained Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A "weakly constrained" MD simulation of the HPAC hairpin in water (wMD) was performed at 300 K, with an arbitrarily choosen force constant K dc of 0.4 kJ/ mol ⅐ Å 2 on the distance constraints and E tc 0.4 kJ/mol on torsion angles. The molecule was immersed in a rectangular box of Monte Carlo TIP3P water molecules.…”
Section: Restrained Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Detailed nmr structures of various H2-family hairpins, having a pyrimidine in the leading position, are now available, 6,9,10,18 from which it is concluded that these minihairpin loops within experimental error share a common basic folding principle, c.q. the position of the first loop residue in the minor groove (-a CTAG-, -CTTG-, -TTTA-, -CCCG-, and -TTTTloop sequences, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…This class of loops has been extensively studied by Altona and collaborators, all at neutral pH (Orbons et al, 1987;Ippel et al, 1992;Ippel, 1993). Common features are the Watson-Crick C·G pair, and the position of the Y base in the minor groove (type II).…”
Section: Structural Features Of the Cccg-loop At Neutral Phmentioning
confidence: 99%
“…In these cases, conformationally constrained oligonucleotides are more suitable models than the pure DNA fragments. 1 Cyclic oligonucleotides are a particular case of constrained oligonucleotides that have been used as models for studying DNA hairpins 2 and quadruplex structures, 3 and have been very useful in many thermodynamic studies. A more general approach to stabilize oligonucleotides is to connect the different strands that make up the structure with a cross-link.…”
mentioning
confidence: 99%